2022
DOI: 10.1021/acs.jmedchem.1c01255
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Hybrid Fasudil Derivatives as a New Approach to the Potential Treatment of Amyotrophic Lateral Sclerosis

Abstract: Hybrid compounds containing structural fragments of the Rho kinase inhibitor fasudil and the NRF2 inducers caffeic and ferulic acids were designed with the aid of docking and molecular mechanics studies. Following the synthesis of the compounds using a peptide-coupling methodology, they were characterized for their ROCK2 inhibition, radical scavenging, effects on cell viability (MTT assay), and NRF2 induction (luciferase assay). One of the compounds ( 1d ) was selected in view of its goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Studies carried out in cell or mouse models with mutations in superoxide dismutase 1 (SOD1) indicate a decrease in the NRF2 signaling pathway [ 49 , 50 ]. These data are consistent with data obtained in lymphoblasts from patients with familial ALS derived from mutations in SOD1 [ 29 , 39 ]. Therefore, the pharmacological modulation of NRF2 as a therapeutic strategy for ALS should be personalized based on the molecular alterations displayed by different types of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies carried out in cell or mouse models with mutations in superoxide dismutase 1 (SOD1) indicate a decrease in the NRF2 signaling pathway [ 49 , 50 ]. These data are consistent with data obtained in lymphoblasts from patients with familial ALS derived from mutations in SOD1 [ 29 , 39 ]. Therefore, the pharmacological modulation of NRF2 as a therapeutic strategy for ALS should be personalized based on the molecular alterations displayed by different types of patients.…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained in this study confirm what we have found in postmortem samples from patients with sALS, namely, a significant increase in the NRF2 antioxidant pathway in both the lumbar spinal cord and the motor cortex. These data in turn confirm the usefulness of the patient lymphoblast cell model as it recapitulates many features of affected motor neurons, such as alterations in TDP-43 homeostasis, oxidative stress, and NRF2 changes [39], and can be used as a suitable cell model platform for preclinical evaluation. Furthermore, the relevance of the NRF2 pathway in ALS pathology is also reinforced by the fact that one haplotype in NFE2L2, which includes three functional promoter SNPs associated with increased protein expression of NRF2, was associated with delayed disease onset of 4 years per allele [40].…”
Section: Discussionsupporting
confidence: 63%
“…Multitarget hybrid fasudil (Figure 14a) derivatives were found as promising molecules for the treatment of ALS by activating the Nrf2 and stimulating the expression of the antioxidant response enzymes HO-1 and NQO1via a KEAP1-dependent mechanism [186]. Acetyl-11-keto-beta-boswellic acid (AKBA) (Figure 14b) is a pentacyclic triterpenoid mixture obtained from Boswellia serrata and other plants, with anti-inflammatory and antioxidant properties [187].…”
Section: Nrf2 In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…2,3 Given the multifactorial and complex molecular nature of ALS, polypharmacology may be considered a promising therapeutic approach, as recently reported. 4 Our long-standing interest in the field prompted us to develop a polypharmacological approach for ALS based on multi-target-directed ligands (MTDLs). 5 Considering the interplay between glutamate excitotoxicity, oxidative stress, and mitochondrial dysfunction, 6 we were interested in combining the properties of 1 and rasagiline (2) into new MTDLs for ALS (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%